Identification of Dysbiosis Related Bacteria from New Zealand’s White Rabbit Intestinal Treated With Lactobacillus plantarum IS-10506 as Probiotics Food Supplementation - Arif S.W. Kusuma ,; Rizky Abdulah ,; Melisa I. Barliana ,; Tiana Milanda ,; Febrina A. Saputri ,; Raden M. Febriyanti ,; Sofa D. Alfian ,; Widya N. Insani ,; Dinda Arditta ,; Devinna ,; Inggrid S. Surono,; Vesara A. Gatera, (Journal of Pharmacy and Nutrition Sciences, 2018)
The gastrointestinal microoganisms encompass thousands of bacterial species that constitute a relatively stable ecosystem inside human body. Dysbiosis is an imbalance condition of beneficiary microbacteria cause by newer microorganism. This research aimed to investigate the effect of L. plantarum IS-10506 as probiotics supplementation on total bacterial and Enterobacteriaceae count; and also to identify the dysbiosis causing bacteria. Total bacterial and Enterobacteriaceae number on both control and test group were determined by Total Plate Count method. Identification of dysbiosis related bacteria were determined by fermentation test, gram staining, and Microbact™ 12A kit. The TPC result of total bacterial population on control group was 222.67 x 106 cfu/ml, while the probiotics induced group was 210.33 x 106 cfu/ml. As for the TPC result for Enterobacteriaceae population from control group was 12.00 x 106 cfu/ml, Enterobacteriaceae population in the probiotics induced group was 11.66 x 106 cfu/ml. Four genera related to dysbiosis has been isolated from the intestinal sample and all are rod-shaped Gram negative bacteria. In conclusion, the use of L. plantarum IS-10506 as food supplementation has reduced the total bacterial count. Four genera of dysbiosis related bacteria has been identified from the intestinal sample which include Eschericia, Serratia, Enterobacter, and Citrobacter.